Diagnostic Dilemma In Stress Fractures: A Report On 3 Different Cases - Karki, Umash; Karki, Netra Bahadur; Duwal Shrestha, Sailendra Kumar; Nepal, Prabin (Nepal Orthopaedic Association Journal, 2024)
Stress fractures are characterized by atraumatic partial or incomplete fractures, encompassing both fatigue and insufficiency fractures. The majority of stress fractures fall within the fatigue type, particularly prevalent in individuals participating in repetitive and intense physical activities for which they are not accustomed. This phenomenon is notably observed in military recruits. The diagnostic identification of stress fractures can pose challenges, often leading to misinterpretations that mimic tumorous or infectious conditions. In this study, we present three illustrative cases to underscore this diagnostic complexity. Two cases initially diagnosed as tumorous and cortical abscesses were later identified as stress fractures. Additionally, a case initially categorized as a stress fracture eventually revealed an underlying manifestation of osteomyelitis. These cases highlight the importance of a comprehensive diagnostic approach in distinguishing stress fractures from conditions with similar clinical presentations.